Geen identiteit zonder oriëntatie in de tijd. Over de noodzaak van chronologie - M. Grever (BMGN: Low Countries Historical Review, 2009)
No Identity without Temporality. Why We Need Chronologies Recently, the Dutch National History Museum launched a concept of five theme-worlds that would serve as the outline of Dutch history. Critics assume that this concept is at loggerheads with a clear chronology; in their view the museum will become a postmodern stew. This contribution investigates the extent to which this critique makes sense. One of the reasons for the critique is that the five-worlds-concept seems to abstract temporality. Indeed, in some theme-worlds different phenomena are gathered under one umbrella. In which case a coherent story with a clear temporality becomes impossible and visitors will get lost. Another reason for the critique is that the concept does not fit the temporality of national political history. There are indeed two theme-worlds which focus on climatic and social-economic processes. However, that does not contradict a chronology, it only indicates a different temporality. This article is part of the forum 'The Dutch National History Museum'.